PENYIDIKAN TINDAK PIDANA PEMALSUAN SURAT AKTA JUAL BELI TANAH DI WILAYAH POLISI RESOR KOTA PEKANBARU - Yohanes Frans; Erdianto '; Rahmad Hendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
The criminal act of forgery stipulated in Chapter XII Book II Criminal Code on forgery, the book lists that are included falsification only form of writings alone, including forgery under Article 263 paragraph (1) of the Criminal Code, which reads: